2nd International Symposium on High-Temperature Metallurgical Processing : Proceedings of a Symposium - Hwang, Jiann-Yang (Minerals, Metals and Materials Society ; Wiley, 2011)
High Temperature Metallurgical Processing contains the proceedings of the Second International Symposium on Thermal Processing of Minerals, Metals and Materials. This symposium explores physical and chemical transformations in materials that have been designed to facilitate the recovery of valuable metals or produce other useful materials. Representatives from both industry and academia focused on the latest innovative high temperature technologies. Because high temperature processes require high energy input, the presenters addressed the need for sustainable technologies that could pro.